Maintaining Indonesian Citizenship: Community Nationalism in Gun Tembawang, West Kalimantan Border in 2022 - Jumiati Jumiati; Syahrul Hidayat (FISIP Universitas Islam Negeri Raden Fatah Palembang, 2023)
The integrity of the state is determined by the strength of nationalism among the inhabitants of the country, and it is also one of the most important things to protect a country.. Nationalism is implemented according to the ideological values of Pancasila that the Indonesian people adhere to. Nationalism in the government is very important to provide policies and regulations and rules for the welfare of society. This interrelational relationship created by nationalism makes it difficult for all parties involved, namely the government and society, to let go of this nationalism. However, this is not seen in Gun Tembawang Hamlet, which is evident from the problems of the peripheral community of Gun Tembawang Hamlet in understanding the concept of nation and applying it in daily life. In this case, the issue of the transfer of citizenship (Gun Tembawang Hamlet) naturally raises the question of why they did it. Why about ±35 family members in Gun Tembawang Hamlet renounced their Indonesian citizenship in favor of Malaysian citizenship, even though they had a history as villagers in Indonesian territory. However, looking further afield, there is economic inequality in Gun Tembawang Hamlet (periphery) which is closely related to the social gap between the center and the periphery. Such a wide gap leads to rebellion by marginalized communities. However, there is something interesting amidst the problem of Malaysian charm and development gap, it turns out that in Gun Tembawang Hamlet, there are still ± 30 heads of families from peripheral communities who retain their Indonesian citizenship. Why these people maintain their Indonesian citizenship regardless of Malaysian charm compared to Indonesia, where the state (Indonesia) does not provide adequate development to meet the development needs of the periphery areas. Therefore, the purpose of this study is to understand nationalism and the activities of peripheral societies, which are often in conflict with the national spirit developed by the state. Specifically, to explain and identify the reasons why the community of Gun Tembawang Hamlet maintains their Indonesian citizenship despite the country not providing adequate development to meet the development needs of the periphery areas. This study also aims to find out about the nationalism of the peripheral society and the economic conditions and situations they face against the attractiveness of Malaysia compared to that of Indonesia. Descriptive research is used as a research method using data sources from books, magazines, websites and interviews. In this study, the author uses Ernest Gellner's theory of Nationalism and Modernisation.